FINANCIAL MANAGEMENT OVERVIEW ON MSME (MICRO, SMALL AND MEDIUM ENTERPRISE) IN MANADO - Pingkan Gabriela Mumu; James D. D. Massie; Ferdinand J. Tumewu (Universitas Sam Ratulangi, 2024)
This qualitative research delves into the financial management practices within Micro, Small, and Medium Enterprises (MSMEs) in Manado, Indonesia. Utilizing a qualitative approach, the study explores descriptive data gathered from interviews, observations, and secondary sources. The primary data emanates from interviews with ten MSME entrepreneurs across various sectors, while secondary data encompasses documentation and literature review. The research involves both qualitative and quantitative data types, emphasizing the qualitative nature of words, images, and non-numeric expressions. Data collection methods include observation, interviews, and literature review, crucial in comprehending the landscape of financial management in MSMEs. The data undergoes qualitative descriptive analysis, involving reduction, display, and conclusion drawing, to elucidate patterns and behavioral aspects of financial management practices. Conducted in Manado over a two-month period, this study aims to shed light on the financial management nuances within MSMEs, underscoring the significance of better financial planning, control, and reporting for their sustenance and growth. Keywords: MSMEs, Financial Management